The development of preventive municipal interventions targeting the mental health of young people: -Leaders’ Perspectives on a Practice-Based Research Project - Petersen, Kirsten Schultz; Moth, Pernille; Jørgensen, Lise; Overgaard, Charlotte (Nordisk Tidsskrift for Helseforskning, 2025)
This article describes the leader’s perspective on a practice-research project aiming to promote young people’s mental health in a Danish municipality. In this article we present how promoting interventions were developed and explore leader’s perspective on their involvement and the co-production of these interventions. The project took place as a research-practice collaboration between a municipality in the Northern part of Denmark and Aalborg University. The researcher’s role was to contribute to knowledge in developing health promoting interventions based on current research and support the formulation of a program theory for interventions. The co-production process was inspired by the Medical Research Councils framework using the core element involving key stakeholders. The leaders together with relevant professionals took part in co-production of two interventions: one targeting competence development of parents to children in 7th grade and one targeting coworkers at the municipal schools and professionals employed at children’s health, teeth and leisure facilities. The following evaluation will show us if the intervention needs further revision before implementation.